Antipsychotic medication versus psychological intervention versus a combination of both in adolescents with first-episode psychosis (MAPS): a multicentre, three-arm, randomised controlled pilot and feasibility study. (September 2020) - Morrison, Anthony P; Pyle, Melissa; Maughan, Daniel; Johns, Louise; Freeman, Daniel; Broome, Matthew R; Husain, Nusrat; Fowler, David; Hudson, Jemma; MacLennan, Graeme; Norrie, John; Shiers, David; et al.
Summary: Background: Evidence for the effectiveness of treatments in early-onset psychosis is sparse. Current guidance for the treatment of early-onset psychosis is mostly extrapolated from trials in adult populations. The UK National Institute for Health and Care Excellence has recommended evaluation of the clinical effectiveness and cost-effectiveness of antipsychotic drugs versus psychological intervention (cognitive behavioural therapy [CBT] and family intervention) versus the combination of these treatments for early-onset psychosis. The aim of this study was to establish the feasibility of a randomised controlled trial of antipsychotic monotherapy, psychological intervention monotherapy, and antipsychotics plus psychological intervention in adolescents with first-episode psychosis. Methods: We did a multicentre pilot and feasibility trial according to a randomised, single-blind, three-arm, controlled design. We recruited participants from seven UK National Health Service Trust sites. Participants were aged 14–18 years; help-seeking; had presented with first-episode psychosis in the past year; were under the care of a psychiatrist; were showing current psychotic symptoms; and met ICD-10 criteria for schizophrenia, schizoaffective disorder, or delusional disorder, or met the entry criteria for an early intervention for psychosis service. Participants were assigned (1:1:1) to antipsychotics, psychological intervention (CBT with optional family intervention), or antipsychotics plus psychological intervention. Randomisation was via a web-based randomisation system, with permuted blocks of random size, stratified by centre and family contact. CBT incorporated up to 26 sessions over 6 months plus up to four booster sessions, and family intervention incorporated up to six sessions over 6 months. Choice and dose of antipsychotic were at the discretion of the treating consultant psychiatrist. Participants were followed up for a maximum of 12 months. The primary outcome was feasibility (ie, data on trial referral and recruitment, session attendance or medication adherence, retention, and treatment acceptability) and the proposed primary efficacy outcome was total score on the Positive and Negative Syndrome Scale (PANSS) at 6 months. Primary outcomes were analysed by intention to treat. Safety outcomes were reported according to as-treated status, for all patients who had received at least one session of CBT or family intervention, or at least one dose of antipsychotics. The study was prospectively registered with ISRCTN, ISRCTN80567433. Findings: Of 101 patients referred to the study, 61 patients (mean age 16·3 years [SD 1·3]) were recruited from April 10, 2017, to Oct 31, 2018, 18 of whom were randomly assigned to psychological intervention, 22 to antipsychotics, and 21 to antipsychotics plus psychological intervention. The trial recruitment rate was 68% of our target sample size of 90 participants. The study had a low referral to recruitment ratio (around 2:1), a high rate of retention (51 [84%] participants retained at the 6-month primary endpoint), a high rate of adherence to psychological intervention (defined as six or more sessions of CBT; in 32 [82%] of 39 participants in the monotherapy and combined groups), and a moderate rate of adherence to antipsychotic medication (defined as at least 6 consecutive weeks of exposure to antipsychotics; in 28 [65%] of 43 participants in the monotherapy and combined groups). Mean scores for PANSS total at the 6-month primary endpoint were 68·6 (SD 17·3) for antipsychotic monotherapy (6·2 points lower than at randomisation), 59·8 (13·7) for psychological intervention (13·1 points lower than at randomisation), and 62·0 (15·9) for antipsychotics plus psychological intervention (13·9 points lower than at randomisation). A good clinical response at 6 months (defined as ≥50% improvement in PANSS total score) was achieved in four (22%) of 18 patients receiving antipsychotic monotherapy, five (31%) of 16 receiving psychological intervention, and five (29%) of 17 receiving antipsychotics plus psychological intervention. In as-treated groups, serious adverse events occurred in eight [35%] of 23 patients in the combined group, two [13%] of 15 in the antipsychotics group, four [24%] of 17 in the psychological intervention group, and four [80%] of five who did not receive any treatment. No serious adverse events were considered to be related to participation in the trial. Interpretation: This trial is the first to show that a head-to-head clinical trial comparing psychological intervention, antipsychotics, and their combination is safe in young people with first-episode psychosis. However, the feasibility of a larger trial is unclear because of site-specific recruitment challenges, and amendments to trial design would be needed for an adequately powered clinical and cost-effectiveness trial that provides robust evidence. Funding: National Institute for Health Research.